Cluster sets and traditional sets elicit similar muscular hypertrophy: a volume and effort‑matched study in resistance‑trained individuals - Vargas-Molina, Salvador; García-Sillero, Manuel; Maroto-Izquierdo, Sergio; Baz‑Valle, Eneko; Bautista‑Mayorga, Borja; Murri, Mora; Schoenfeld, Brad J.; Benítez-Porres, Javier (Springer Nature, 2025)
Background and Objective Previous studies examining the effects of cluster sets (CS) compared to traditional sets (TS) protocols on muscle hypertrophy have primarily equated to volume load. This inevitably has resulted in a lower number of repetitions performed in TS compared to CS, thereby leading to a suboptimal hypertrophic stimulus. The present study aimed to compare the impact of CS and TS protocols, both performed with the same number of sets and repetitions, but with loads adjusted to the same range of repetitions in reserve (RIR) on muscle hypertrophy. Methods Ten resistance-trained volunteers (7 men and 3 women, 21.0 ± 1.5 years, 64.3 ± 6.9 kg, and 169.3 ± 6.2 cm) partici- pated in this study. Participants performed two training protocols over an 8-week period, with two weekly sessions consisting of 5 sets of 12 repetitions of the leg press and leg extension exercises. The study employed a within-participant, unilateral design where one limb performed a TS protocol and the contralateral limb performed 3 clusters of 4 repetitions with a 20-s intra-set rest period of the same exercises (CS). Muscle thickness was assessed via ultrasound and thigh lean tissue mass was assessed by dual-energy X-ray absorptiometry pre- and post-study. Results Results showed similar increases in muscle thickness (p < 0.001, ES = 0.56, and p = 0.012, ES = 0.42, respectively) and lean tissue mass (p = 0.002, ES = 0.11, and p < 0.001, ES = 0.13, respectively) in both CS and TS conditions. Conclusion In conclusion, when sets, repetitions, and load adjustments were equalized based on RIR, a CS protocol elicits similar increases in muscle thickness and lean mass compared to a TS protocol
Keywords: Educación física; Rest-pause training; Hypertrophy; Muscle-mass; Drop sets; Body composition; Body building